Carbon-silicon composite material and preparation method thereof, negative pole piece and lithium ion battery
By nano-nanization of silicon and forming a multi-layer heterogeneous carbon coating on its surface, the structural damage problem of silicon due to volume changes in lithium-ion batteries is solved, and more stable cycling performance and longer service life are achieved.
Patent Information
- Application Number
- CN202311361756.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
In lithium-ion batteries, silicon as the negative electrode material, during charging and discharging, resulting in powderization and structural damage due to volume expansion and contraction, affecting the cycling performance and service life of the battery.
By nano-nanization of the silicon source and multi-heterogeneized carbon coating on the outside of the nano-silicon, a carbon-silicon composite is formed to reduce the volume effect of the silicon and provide expansion strength and space.
It improves the cycle stability and rate performance of carbon-silicon composite materials and extends the service life of the battery.
Smart Images

Figure CN119858906A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium-ion batteries, and in particular to a carbon-silicon composite material and a preparation method thereof, a negative electrode sheet and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries have become an ideal chemical power source for modern communications, portable electronic products, and hybrid vehicles due to their high specific energy, long charge and discharge life, no memory effect, low self-discharge rate, fast charging, no pollution, wide operating temperature range, and safety and reliability. The current commercial negative electrode material is graphite, with a theoretical specific capacity of 372mAh·g -1 , can no longer meet the demand for high energy density batteries, so it is necessary to develop high-capacity negative electrode active materials.
[0003] Silicon has a high theoretical specific capacity (4200mA hg -1 ), low operating voltage and other characteristics have attracted extensive research, and it is abundant in the earth's crust, low cost, and environmentally friendly, making it one of the most promising negative electrode materials for next-generation lithium-ion batteries. However, silicon produces huge volume expansion and contraction during the charge and discharge process (the volume change rate is close to 300%), which can cause silicon pulverization and structural damage, resulting in contact and separation between battery materials and between them and the current collector, causing its capacity to decay rapidly, seriously affecting the battery's cycle performance and service life. Summary of the invention
[0004] The purpose of the present disclosure is to provide a carbon-silicon composite material and a preparation method thereof, a negative electrode plate and a lithium-ion battery, and to prepare a carbon-silicon composite material with high first coulombic efficiency and stable cycle by a method including silicon nano-crystallization and silicon-carbon composite.
[0005] In order to achieve the above object, the present disclosure provides a method for preparing a carbon-silicon composite material in a first aspect, comprising the following steps:
[0006] S1, mixing a silicon source with an organic solvent, and crushing the mixture to obtain a nano-silicon slurry;
[0007] S2, contacting the nano-silicon slurry with a first carbon source to perform an in-situ coating reaction to obtain a primary coated nano-silicon slurry, wherein the first carbon source includes an organic acid;
[0008] S3, contacting the primary coated nano-silicon slurry with a second carbon source to perform a secondary in-situ coating reaction to obtain a secondary coated nano-silicon slurry, wherein the second carbon source includes an organic amine;
[0009] S4, contacting the secondary coated nano-silicon slurry with a carbonizable binder and a third carbon source, performing three in-situ coating reactions to obtain a carbon-silicon composite material precursor, wherein the third carbon source includes a graphite carbon source;
[0010] S5, calcining the carbon-silicon composite material precursor under an inert atmosphere.
[0011] Optionally, in step S1, the silicon source is elemental silicon powder; optionally, the elemental silicon powder includes single crystal silicon and / or polycrystalline silicon; optionally, the particle size of the elemental silicon powder ranges from 1 μm to 10 μm;
[0012] Optionally, the organic solvent is selected from one or more of an alcohol organic solvent, a hydrocarbon organic solvent and a benzene organic solvent;
[0013] Preferably, the alcohol organic solvent is selected from one or more of ethanol, propanol and isopropanol;
[0014] The hydrocarbon organic solvent is selected from one or more of hexane, cyclohexane and isooctane;
[0015] The benzene organic solvent is selected from one or more of benzene, toluene and xylene;
[0016] Preferably, the weight of the silicon source is 3 g to 20 g, preferably 5 g to 15 g, relative to 100 mL of the organic solvent.
[0017] Optionally, in step S1, the crushing treatment method includes mechanized crushing treatment by sand milling; preferably, the conditions of the mechanized crushing treatment by sand milling include: sand milling in a sand mill under an inert atmosphere, the sand mill speed is 2000r / min to 2500r / min, and the sand milling time is 4 to 50h, preferably 6 to 20h;
[0018] Preferably, the D50 particle size range of the solid nano-silicon in the nano-silicon slurry obtained through the crushing treatment is 5 nm to 150 nm, preferably 30 nm to 100 nm.
[0019] Optionally, in step S2, the weight ratio of the first carbon source to the silicon source is 1:0.2-5, preferably 1:0.5-5;
[0020] Preferably, the organic acid comprises one or more of a hydroxyl-containing organic carboxylic acid and a hydroxyl-containing carboxylic acid ester;
[0021] Optionally, the hydroxyl-containing organic carboxylic acid is selected from one or more of tartaric acid, citric acid, lactobionic acid, malic acid and glutamic acid;
[0022] Preferably, the hydroxyl-containing carboxylic acid ester comprises ascorbic acid;
[0023] Preferably, the organic acid is selected from one or more of citric acid, tartaric acid and malic acid.
[0024] Optionally, in step S2, the conditions of the primary in-situ coating reaction include: reaction temperature of 15°C to 60°C, reaction time of 0.25h to 4h; preferably, reaction temperature of 20°C to 30°C, reaction time of 0.5h to 2h; optionally, stirring rate of 200r / min to 600r / min, preferably 300r / min to 450r / min.
[0025] Optionally, in step S3, the weight ratio of the second carbon source to the first carbon source is 0.1 to 2:1, preferably 0.3 to 1.2:1, and more preferably 0.4 to 1:1;
[0026] Preferably, the organic amine is selected from one or more of melamine and its ammonium salt, dopamine and its ammonium salt, hexamethylenetetramine and its ammonium salt; preferably, the organic amine is selected from one or both of dopamine and melamine.
[0027] Optionally, in step S3, the conditions of the secondary in-situ coating reaction include: the reaction temperature is 15°C to 60°C, and the reaction time is 0.25h to 4h; preferably, the reaction temperature is 20°C to 30°C, and the reaction time is 0.5h to 2h; optionally, the stirring rate is 200r / min to 600r / min, preferably 300r / min to 450r / min.
[0028] Optionally, in step S4, the weight ratio of the carbonizable binder to the silicon source is 0.1 to 2:1, preferably 0.1 to 1:1;
[0029] Optionally, the carbonizable binder is selected from one or more of asphalt, sodium carboxymethyl cellulose and lithium carboxymethyl cellulose;
[0030] Preferably, in step S4, the weight ratio of the third carbon source to the silicon source is 4 to 50:1, preferably 6 to 40:1;
[0031] Optionally, the graphite carbon source is selected from one or more of natural graphite, artificial graphite and flake graphite; preferably, the graphite carbon source is selected from one or more of natural graphite and artificial graphite having a spherical structure.
[0032] Optionally, in step S4, the conditions of the three in-situ coating reactions include: a reaction temperature of 15°C to 60°C, a reaction time of 0.25h to 4h; preferably, a reaction temperature of 20°C to 30°C, a reaction time of 0.5h to 2h; optionally, a stirring rate of 200r / min to 600r / min, preferably 300r / min to 400r / min;
[0033] Preferably, step S4 further comprises spray drying the mixed slurry obtained by the three in-situ coating reactions to obtain the carbon-silicon composite material precursor; preferably, the conditions of the spray drying process include: a feed temperature of 120°C to 220°C, an outlet temperature of 80°C to 120°C, a carrier gas flow rate of 10L / min to 100L / min, an inlet pressure of 0.1MPa to 0.6MPa, and the carrier gas is selected from one or more of nitrogen and argon;
[0034] Preferably, the feed temperature is 140°C to 180°C, the outlet temperature is 80°C to 100°C, the carrier gas flow rate is 30L / min to 60L / min, and the inlet pressure is 0.2MPa to 0.4MPa.
[0035] Optionally, in step S5, the conditions of the calcination treatment include: a calcination temperature of 600°C to 1100°C, and a calcination time of 0.5h to 6h; preferably, a calcination temperature of 800°C to 1000°C, and a calcination time of 1h to 3h;
[0036] Optionally, the heating rate is 1°C / min to 10°C / min, preferably 3°C / min to 5°C / min;
[0037] The inert atmosphere is selected from one or more of argon and nitrogen.
[0038] A second aspect of the present disclosure provides a carbon-silicon composite material prepared according to the method described in the first aspect of the present disclosure.
[0039] A third aspect of the present disclosure provides a carbon-silicon composite material, which includes nano-silicon and a multi-layer heterogeneous carbon coating layer coated on the surface of the silicon matrix; the multi-layer heterogeneous carbon coating layer includes a first carbon coating layer, a second carbon coating layer and a third carbon coating layer stacked in an outward direction from the surface of the nano-silicon; the second carbon coating layer contains nitrogen.
[0040] Optionally, based on the total weight of the carbon-silicon composite material, the silicon content in the carbon-silicon composite material is 1 wt% to 20 wt%, the carbon content is 80 wt% to 97 wt%, the nitrogen content is 0.1 wt% to 2 wt%, and the oxygen content is 1 wt% to 10 wt%;
[0041] Preferably, the carbon-silicon composite material contains 1% to 10% by weight of silicon, 80% to 90% by weight of carbon, 0.1% to 0.5% by weight of nitrogen, and 3% to 10% by weight of oxygen.
[0042] Optionally, the first carbon coating layer is an organic acid carbon coating layer, the second carbon coating layer is an organic amine carbon coating layer, and the third carbon coating layer is a graphite carbon coating layer;
[0043] Preferably, in the carbon-silicon composite material, the total thickness of the multi-layer heterogeneous carbon coating layer is 10nm to 150nm, preferably 20nm to 100nm;
[0044] Preferably, the thickness of the first carbon coating layer is 5nm to 40nm, the thickness of the second carbon coating layer is 5nm to 40nm, and the thickness of the third carbon coating layer is 10nm to 50nm;
[0045] Optionally, the carbon-silicon composite material has an average particle size of 1 μm to 50 μm and a BET specific surface area of 1 m 2 / g~50m 2 / g; Preferably, the average particle size of the carbon-silicon composite material is 3 μm to 30 μm, and the BET specific surface area is 1 m 2 / g~10m 2 / g.
[0046] A fourth aspect of the present disclosure provides a negative electrode plate, comprising the carbon-silicon composite material described in the second aspect or the third aspect of the present disclosure.
[0047] A fifth aspect of the present disclosure provides a lithium-ion battery, comprising the negative electrode sheet described in the fourth aspect of the present disclosure.
[0048] Through the above technical scheme, the present disclosure provides a carbon-silicon composite material and a preparation method thereof, a negative electrode plate and a lithium-ion battery. The present disclosure first nanosizes the silicon source to reduce the volume effect of silicon, thereby reserving sufficient expansion space for the contraction and expansion of silicon particles, and then coats the outside of the nano-silicon with multiple heterogeneous carbon coating layers. The multiple heterogeneous carbon coating layers are used to provide sufficient strength and space for the expansion of silicon, thereby improving its cycle stability performance, and at the same time can provide structural support for the rate performance of the material.
[0049] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0051] Figure 1 This is a TEM photo of the carbon-silicon composite material prepared in Preparation Example 1 of the present disclosure;
[0052] Figure 2 This is a SEM photo of the carbon-silicon composite material prepared in Preparation Example 1 of the present disclosure;
[0053] Figure 3This is the XRD spectrum of the carbon-silicon composite material prepared in Preparation Example 1 of the present disclosure;
[0054] Figure 4 This is a first charge and discharge curve diagram of the carbon-silicon composite material prepared in Preparation Example 1 of the present disclosure;
[0055] Figure 5 This is a charge-discharge cycle curve diagram of the carbon-silicon composite material prepared in Preparation Example 1 of the present disclosure;
[0056] Figure 6 This is a rate performance cycle curve diagram of the carbon-silicon composite material prepared in Preparation Example 1 of the present disclosure. DETAILED DESCRIPTION
[0057] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0058] In this disclosure, except for the contents explicitly described, any matters or items not mentioned are directly applicable to the contents known in the art without any changes. Moreover, any embodiment described herein can be freely combined with one or more other embodiments described herein, and the technical solutions or technical ideas formed thereby are regarded as part of the original disclosure or record of this disclosure, and should not be regarded as new contents not disclosed or anticipated herein, unless a person skilled in the art considers that the combination is obviously unreasonable.
[0059] All features disclosed in this disclosure may be combined arbitrarily, and these combinations shall be understood as the contents disclosed or recorded in this disclosure, unless a person skilled in the art considers that the combination is obviously unreasonable, and shall be deemed to be specifically disclosed and recorded in this disclosure. The numerical points disclosed in this specification, unless otherwise specified, include not only the numerical points specifically disclosed in the embodiments, but also the endpoints of each numerical range in the specification, and the range of any combination of these numerical points shall be deemed to be the range disclosed or recorded in this disclosure.
[0060] Technical and scientific terms in the present disclosure shall be based on their definitions if they are defined, and shall be understood according to the common meaning in the art if no definitions are given.
[0061] The term "nano-silicon" is defined as silicon having an average particle size (D50 particle size) of 5 nm to 500 nm.
[0062] The term "inert gas" is defined as a gas that has no appreciable effect on the electrochemical performance of the composite material.
[0063] The term "soluble" means soluble in the solvent in which it is used.
[0064] The present disclosure provides a method for preparing a carbon-silicon composite material, comprising the following steps:
[0065] S1, mixing a silicon source with an organic solvent, and crushing the mixture to obtain a nano-silicon slurry;
[0066] S2, contacting the nano-silicon slurry with a first carbon source to perform an in-situ coating reaction to obtain a primary coated nano-silicon slurry in which an organic acid and nano-silicon are combined, wherein the first carbon source includes an organic acid;
[0067] S3, contacting the primary coated nano-silicon slurry with a second carbon source to perform a secondary in-situ coating reaction to obtain a secondary coated nano-silicon slurry obtained by a secondary in-situ reaction of an organic amine and an organic acid, wherein the second carbon source includes an organic amine;
[0068] S4, contacting the secondary coated nano-silicon slurry with a carbonizable binder and a third carbon source, performing three in-situ coating reactions to obtain a carbon-silicon composite material precursor, wherein the third carbon source includes a graphite carbon source;
[0069] S5, calcining the carbon-silicon composite material precursor under an inert atmosphere.
[0070] The present disclosure provides a method for preparing a carbon-silicon composite material. The present disclosure firstly nanosizes a silicon source to reduce the volume effect of silicon and reserve sufficient expansion space for the contraction and expansion of silicon particles. Then, multiple heterogeneous carbon coating layers are coated on the outside of the nano-silicon. The multiple heterogeneous carbon coating layers are utilized to provide sufficient strength and space for the expansion of silicon, thereby improving its cyclic stability performance and providing structural support for the rate performance of the material.
[0071] According to the present disclosure, the first carbon source is a hydroxyl-containing organic carboxylic acid or carboxylate. The inventors of the present disclosure have found that the hydroxyl-containing organic carboxylic acid or carboxylate can react with the reactive silicon sites generated after the silicon is crushed, uniformly covering the silicon surface to obtain in-situ coated nano-silicon; after adding the second carbon source, the organic amine can react in situ with the hydroxyl-containing organic carboxylic acid or carboxylate to form a secondary coating on the silicon; and adding a binder and a graphite-based carbon source can form a tertiary coating, and finally form a multi-layer heterogeneous carbon coating layer on the surface of the nano-silicon.
[0072] In one embodiment, in step S1, the silicon source is elemental silicon powder; optionally, the elemental silicon powder includes single crystal silicon and / or polycrystalline silicon; optionally, the particle size of the elemental silicon powder ranges from 1 μm to 10 μm; optionally, the organic solvent is selected from one or more of an alcohol organic solvent, a hydrocarbon organic solvent and a benzene organic solvent;
[0073] Preferably, the alcohol organic solvent is selected from one or more of ethanol, isopropanol and propanol;
[0074] The hydrocarbon organic solvent is selected from one or more of hexane, cyclohexane and isooctane;
[0075] The benzene organic solvent is selected from one or more of benzene, toluene and xylene;
[0076] Preferably, the organic solvent is selected from one or both of isopropanol and ethanol.
[0077] In a preferred embodiment, in step S1, the weight of the silicon source is 3 g to 20 g, preferably 5 g to 15 g, relative to 100 mL of the organic solvent. Preferably, the solid content of the nano-silicon slurry obtained in step S1 is 2 wt% to 20 wt%, preferably 3 wt% to 15 wt%, calculated as silicon.
[0078] In one embodiment, in step S1, the crushing treatment method includes a sanding mechanized crushing treatment; preferably, the conditions of the sanding mechanized crushing treatment include: the sanding process is carried out under an inert atmosphere and the sand mill speed is 2000r / min to 2500r / min. The sanding device used in the present disclosure is a device of conventional structure in the art.
[0079] In a preferred embodiment, the average particle size (D50) of the solid nano-silicon in the nano-silicon slurry obtained by the crushing process is in the range of 5 nm to 150 nm, preferably 30 nm to 100 nm.
[0080] In one embodiment, in step S2, the weight ratio of the first carbon source to the silicon source is 1:0.2-5, preferably 1:0.5-5.
[0081] In a preferred embodiment, the organic acid comprises one or more of a hydroxyl-containing organic carboxylic acid and a hydroxyl-containing carboxylic acid ester;
[0082] Optionally, the hydroxyl-containing organic carboxylic acid is selected from one or more of tartaric acid, citric acid, lactobionic acid, malic acid and ascorbic acid;
[0083] Preferably, the hydroxyl-containing carboxylic acid ester comprises ascorbic acid;
[0084] Preferably, the organic acid is selected from one or more of citric acid, tartaric acid and malic acid.
[0085] In a specific embodiment, in step S2, the conditions of the in-situ coating reaction include: the reaction temperature is 15°C to 60°C, and the reaction time is 0.25h to 4h; preferably, the reaction temperature is 20°C to 30°C, and the reaction time is 0.5h to 2h; optionally, the stirring rate is 200r / min to 600r / min, preferably 300r / min to 450r / min.
[0086] In one embodiment, in step S3, the weight ratio of the second carbon source to the first carbon source is 0.1 to 2:1, preferably 0.3 to 1.2:1, and more preferably 0.4 to 1:1.
[0087] In a preferred embodiment, the organic amine is selected from one or more of melamine and its ammonium salt, dopamine and its ammonium salt, and hexamethylenetetramine and its ammonium salt; preferably, the organic amine is selected from one or more of dopamine and melamine. The primary coated nano-silicon slurry disclosed herein uses hydroxyl-containing organic carboxylic acids and hydroxyl-containing carboxylic acid esters as the first carbon source. The abundant alcoholic hydroxyl groups and carboxyl hydroxyl groups in the first carbon source have strong binding force with the phenolic hydroxyl groups and amino groups in the organic amine (such as dopamine) of the second carbon source, so that the organic amine is evenly distributed on the surface of the nano-silicon precursor, thereby improving the secondary in-situ coating effect.
[0088] In a specific embodiment, in step S3, the conditions of the secondary in-situ coating reaction include: the reaction temperature is 15°C to 60°C, and the reaction time is 0.25h to 4h; preferably, the reaction temperature is 20°C to 30°C, and the reaction time is 0.5h to 2h; optionally, the stirring rate is 200r / min to 600r / min, preferably 300r / min to 450r / min.
[0089] In one embodiment, in step S4, the weight ratio of the carbonizable binder to the silicon source is 0.1 to 2:1, preferably 0.1 to 1:1;
[0090] Optionally, the carbonizable binder is selected from one or more of asphalt, sodium carboxymethyl cellulose and lithium carboxymethyl cellulose;
[0091] Preferably, in step S4, the weight ratio of the third carbon source to the silicon source is 4 to 50:1, preferably 6 to 40:1;
[0092] Optionally, the graphite carbon source is selected from one or more of natural graphite, artificial graphite and flake graphite; preferably, the graphite carbon source is selected from one or more of natural graphite and artificial graphite having a spherical structure.
[0093] In one embodiment, in step S4, the conditions of the three in-situ coating reactions include: a reaction temperature of 15°C to 60°C, and a reaction time of 0.25h to 4h; preferably, the reaction temperature is 20°C to 30°C, and the reaction time is 0.5h to 2h; optionally, the stirring rate is 200r / min to 600r / min, preferably 300r / min to 400r / min.
[0094] In a specific embodiment, step S4 further comprises: removing solvent from the mixed slurry obtained by the three in-situ coating reactions to obtain the carbon-silicon composite material precursor.
[0095] In the present disclosure, the solvent removal treatment can be carried out by a conventional method in the art, preferably a spray drying treatment. In a specific implementation method, the conditions of the spray drying treatment include: a feed temperature of 120°C to 220°C, an outlet temperature of 80°C to 120°C, a carrier gas flow rate of 10L / min to 100L / min, an inlet pressure of 0.1MPa to 0.6MPa, and the carrier gas is selected from one or more of nitrogen and argon;
[0096] Preferably, the feed temperature is 140°C to 180°C, the outlet temperature is 80°C to 100°C, the carrier gas flow rate is 30L / min to 60L / min, and the inlet pressure is 0.2MPa to 0.4MPa.
[0097] In one embodiment, in step S5, the conditions of the calcination treatment include: a calcination temperature of 600°C to 1100°C, and a calcination time of 0.5h to 6h; preferably, a calcination temperature of 800°C to 1000°C, and a calcination time of 1h to 3h; optionally, a heating rate of 1°C / min to 10°C / min, preferably 3°C / min to 5°C / min;
[0098] The inert atmosphere is selected from one or more of argon and nitrogen.
[0099] A second aspect of the present disclosure provides a carbon-silicon composite material prepared according to the method described in the first aspect of the present disclosure.
[0100] A third aspect of the present disclosure provides a carbon-silicon composite material, which includes nano-silicon and a multi-layer heterogeneous carbon coating layer coated on the surface of the silicon matrix; the multi-layer heterogeneous carbon coating layer includes a first carbon coating layer, a second carbon coating layer and a third carbon coating layer stacked in an outward direction from the surface of the nano-silicon; the second carbon coating layer contains nitrogen.
[0101] In one embodiment, the nano-silicon may be in a conventional form in the art, such as nanoparticles, nanowires or nanosheets.
[0102] In one embodiment, the multi-layer heterogeneous carbon coating comprises carbon, nitrogen and oxygen.
[0103] In a preferred embodiment, the first carbon coating layer in the multi-layer heterogeneous carbon coating layer is an organic acid carbon coating layer, the second carbon coating layer is an organic amine carbon coating layer, and the third carbon coating layer is a graphite carbon coating layer.
[0104] In a specific embodiment, based on the total weight of the carbon-silicon composite material, the silicon content in the carbon-silicon composite material is 1 wt% to 20 wt%, the carbon content is 80 wt% to 97 wt%, the nitrogen content is 0.1 wt% to 2 wt%, and the oxygen content is 1 wt% to 10 wt%;
[0105] Preferably, the carbon-silicon composite material contains 1% to 10% by weight of silicon, 80% to 90% by weight of carbon, 0.1% to 0.5% by weight of nitrogen, and 3% to 10% by weight of oxygen.
[0106] In a preferred embodiment, in the carbon-silicon composite material, the total thickness of the multi-layer heterogeneous carbon coating layer is 10nm to 150nm, preferably 20nm to 100nm;
[0107] Preferably, the thickness of the first carbon coating layer is 5 nm to 40 nm, the thickness of the second carbon coating layer is 5 nm to 40 nm, and the thickness of the third carbon coating layer is 10 nm to 50 nm.
[0108] In a specific embodiment, the carbon-silicon composite material has an average particle size of 1 μm to 50 μm and a BET specific surface area of 1 m 2 / g~50m 2 / g; Preferably, the average particle size of the carbon-silicon composite material is 3 μm to 30 μm, and the BET specific surface area is 1 m 2 / g~10m 2 / g.
[0109] In one embodiment, the secondary particle size of the carbon-silicon composite material can be 1 μm to 50 μm. The secondary particle size is related to the drying form and operating conditions of the coated and modified nano-silicon obtained in different steps. For example, products with different secondary particle sizes can be obtained by using different types of spray dryers and different operating conditions. These are all existing knowledge in the field, and those skilled in the art can select appropriate equipment and operating conditions according to actual needs.
[0110] A fourth aspect of the present disclosure provides a negative electrode plate, comprising the carbon-silicon composite material described in the second aspect or the third aspect of the present disclosure.
[0111] In a specific embodiment, the negative electrode plate is prepared by a method comprising the following steps:
[0112] The carbon-silicon composite material, the negative electrode conductive material and the binder are mixed in a weight ratio of 70-95:2-10:3-20 to obtain a negative electrode slurry; the slurry is coated on a copper foil and dried to obtain a negative electrode sheet.
[0113] In a specific embodiment, the negative electrode active material is selected from one or more of acetylene black, carbon nanotubes and graphene;
[0114] The binder is selected from one or more of sodium carboxymethyl cellulose, polystyrene butadiene copolymer (SBR) and lithium carboxymethyl cellulose.
[0115] The specific operations and conditions in the preparation process of the negative electrode sheet in the present disclosure are conventional operations and conditions in the art.
[0116] A fifth aspect of the present disclosure provides a lithium-ion battery, comprising the negative electrode sheet described in the fourth aspect of the present disclosure.
[0117] In the present disclosure, the positive electrode, electrolyte and separator used in the lithium-ion battery can be various materials conventionally applicable in the art, and the present disclosure has no particular limitation on this. For example, the separator can be selected from any one of a polyethylene film, a polypropylene film, and a polyethylene and polypropylene composite film. And the composition of the lithium-ion battery provided in the present disclosure is a conventional composition in the art.
[0118] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.
[0119] The carbon coating structure on the silicon surface was characterized by transmission electron microscopy (TEM). The model of the TEM used was JEM-2100 (JEOL Ltd.), and the test conditions of the TEM were: acceleration voltage was 200 kV.
[0120] Instruments and methods for elemental analysis: Carbon content was tested on a TA5000 thermal analyzer in an air atmosphere with a heating rate of 10°C / min over a temperature range from room temperature (25°C) to 1000°C. Nitrogen and oxygen content were tested on an ON5500 nitrogen and oxygen analyzer produced by Gangyan NAK Testing Technology Co., Ltd. with high-purity helium as the carrier gas.
[0121] Instrument and method for particle size test: The average particle size of nano silicon after sand grinding was measured by using the British Mastersizer 3000 particle size analyzer, and the parameter setting was: the light shielding degree was 5.99%. The average particle size of the finished material was measured by using the British Mastersizer 2000 particle size analyzer, and the parameter setting was: the light shielding degree was 10%.
[0122] Instruments and methods for XPS testing: X-ray photoelectron spectroscopy was performed on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific. The excitation source was monochromatic Al Kα X-rays with an energy of 1486.6 eV, a power of 150 W, a narrow scan with a penetration energy of 30 eV, and a basic vacuum of 6.5 × 10-10 mbar during the analysis. Data processing was performed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module. The samples were dried in a helium atmosphere at 150 ° C and 1 standard atmosphere for 3 hours before testing.
[0123] Electrochemical testing instrument: CT3002A battery testing system of Wuhan Blue Electric Electronics Co., Ltd.
[0124] Sand mill model: VB0.6Q nano sand mill produced by Suzhou Weige Nano Technology Co., Ltd.
[0125] Spray dryer model: B-290 from BUCHI, Switzerland, including B-295 inert gas circulation device, using nitrogen as carrier gas for spray drying.
[0126] Preparation Example 1
[0127] (1) 75 g of silicon powder (single crystal silicon, silicon purity of 99.999%, particle size range of 2 μm to 10 μm) was added to 1500 mL of ethanol solution, and the mixture was sand-milled at a speed of 2200 r / min for 8 h in a sand mill under nitrogen protection to obtain a nano-silicon slurry. The weight of the silicon powder was 5 g relative to 100 mL of organic solvent, and the average particle size D50 of solid nano-silicon in the obtained nano-silicon slurry was 29.1 nm;
[0128] (2) taking 40 mL of the nano-silicon slurry prepared in step (1) (silicon mass is 2 g), adding 1.0 g of ascorbic acid (first carbon source), stirring and dissolving, the weight ratio of the first carbon source to the silicon source is 1:2, and the conditions of the primary in-situ coating reaction include: reaction temperature of 25 ° C, reaction time of 2 h, stirring rate of 450 r / min, and obtaining ascorbic acid primary coated nano-silicon slurry;
[0129] (3) adding 0.5 g of dopamine hydrochloride (second carbon source) to the ascorbic acid primary coated nano-silicon slurry prepared in step (2), with the weight ratio of the second carbon source to the first carbon source being 0.5:1, and continuing stirring at room temperature for 1 h at a stirring rate of 450 r / min to obtain a nano-silicon slurry coated with dopamine and ascorbic acid by in-situ reaction;
[0130] (4) Take 1.0g of asphalt and 0.4g of carboxymethyl cellulose (a total of 1.4g of carbonizable binder, and a weight ratio of the carbonizable binder to the silicon source of 0.7:1) and add them to the nano-silicon slurry prepared in step (3), continue stirring at room temperature for 1h, then add 20g of artificial graphite (a third carbon source, and a weight ratio of the third carbon source to the silicon source of 10:1) and further mix, the reaction temperature is 30°C, the reaction time is 3h, the stirring rate is 300r / min, after stirring evenly, spray drying, the feed temperature is 160°C, the outlet temperature is 80°C, the carrier gas flow rate is 40L / min, the inlet pressure is 0.2MPa, and the carrier gas is nitrogen to obtain a silicon-carbon coated precursor;
[0131] (5) The obtained silicon-carbon coated precursor was placed in a porcelain boat and heated in a tube furnace at 5 °C min under an argon atmosphere. -1 The temperature was raised to 900°C at a rate of , then kept at that temperature for 3 hours, and naturally cooled to room temperature to obtain a silicon-carbon coated material.
[0132] The TEM photo of the silicon-carbon coated material obtained in this preparation example is shown in Figure 1 As shown, it can be seen that the silicon-carbon coating material of this preparation example has multiple layers of heterogeneous carbon coating layers with obvious boundaries, including 3 layers of carbon coating layers from the inside to the outside, and the thickness range of each carbon coating layer and the total thickness range of the carbon coating layer are listed in Table 1;
[0133] The SEM photo of the silicon-carbon coated material obtained in this preparation example is shown in Figure 2 As shown, it can be seen that the silicon-carbon coated material obtained in this preparation example is spherical in shape, has a regular particle size, and is densely coated.
[0134] The XRD spectrum of the silicon-carbon coated material obtained in this preparation example is as follows Figure 3 As shown, it can be seen that the silicon-carbon coated material obtained in this preparation example contains characteristic peaks of graphite and silicon, and no other impurity peaks. The nano-silicon and graphite in the prepared silicon-carbon coated material maintain the physicochemical characteristics of the material, which is beneficial to maintaining the electrochemical intrinsic properties of the material.
[0135] Comparative Example 1
[0136] This comparative example prepares a nano-carbon silicon composite material by referring to the method in Preparation Example 1. The difference from Preparation Example 1 is that dopamine hydrochloride is not added in step (3) of this comparative example. The rest of the process is the same as Preparation Example 1 to prepare an ascorbic acid-coated silicon-carbon coated material.
[0137] Comparative Example 2
[0138] This comparative example refers to the method in Preparation Example 1 to prepare a nano-carbon silicon composite material. The difference from Preparation Example 1 is that this comparative example does not include step (2) and does not add an organic acid. The remaining process is the same as Preparation Example 1 to prepare a dopamine hydrochloride-coated silicon-carbon coated material.
[0139] Comparative Example 3
[0140] This comparative example prepares a nano-carbon silicon composite material by referring to the method in Preparation Example 1. The difference from Preparation Example 1 is that this comparative example does not include step (2) and step (3), and neither ascorbic acid nor dopamine hydrochloride is added.
[0141] Comparative Example 4
[0142] This comparative example refers to the method in Preparation Example 1 to prepare a nano-carbon silicon composite material. The difference from Preparation Example 1 is that: steps (2) to (4) are combined and carried out, that is, ascorbic acid, dopamine hydrochloride and asphalt are added to the nano-silicon slurry obtained in step (1) and mixed with carboxymethyl cellulose, and then in-situ coating is carried out. The coating conditions are: reaction temperature is 25°C, reaction time is 2h, stirring rate is 450r / min, spray drying after stirring evenly, feed temperature is 160°C, outlet temperature is 85°C, carrier gas flow rate is 40L / min, inlet pressure is 0.2MPa, and carrier gas is nitrogen to obtain a coated precursor; then step (5) is carried out the same as in Preparation Example 1 to obtain a silicon-carbon coated material.
[0143] Preparation Example 2
[0144] (1) 75 g of silicon powder (single crystal silicon, silicon purity of 99.999%, particle size range of 2 μm to 10 μm) was added to 1500 mL of isopropanol solution, and the mixture was sand-milled at a speed of 2300 r / min for 8 h in a sand mill under nitrogen protection to obtain a nano-silicon slurry. The weight of the silicon powder was 5 g relative to 100 mL of organic solvent, and the average particle size D50 of solid nano-silicon in the obtained nano-silicon slurry was 42.7 nm;
[0145] (2) taking 40 mL of the nano-silicon slurry prepared in step (1) (silicon mass is 2 g), adding 2.0 g of citric acid (first carbon source), stirring and dissolving and dispersing, the weight ratio of the first carbon source to the silicon source is 1:1, and the conditions of the primary in-situ coating reaction include: reaction temperature of 25°C, reaction time of 1 h, stirring rate of 450 r / min, and obtaining citric acid primary coated nano-silicon slurry;
[0146] (3) adding 2.0 g of dopamine hydrochloride (second carbon source) to the citric acid primary coated nano-silicon slurry prepared in step (2), with the weight ratio of the second carbon source to the first carbon source being 1:1, and continuing stirring for 1 h at room temperature (25° C.) at a stirring rate of 450 r / min to obtain a nano-silicon slurry coated by in-situ reaction of dopamine and citric acid;
[0147] (4) Take 2.0g of asphalt (2.0g of carbonizable binder, the weight ratio of carbonizable binder to silicon source is 1:1) and add it to the nano-silicon slurry prepared in step (3), continue stirring at room temperature for 1h, then add 20g of artificial graphite (the third carbon source, the weight ratio of the third carbon source to the silicon source is 10:1) and further mix, the reaction temperature is 25°C, the reaction time is 1h, the stirring rate is 300r / min, after stirring evenly, spray drying, the feed temperature is 160°C, the outlet temperature is 80°C, the carrier gas flow rate is 50L / min, the inlet pressure is 0.2MPa, and the carrier gas is nitrogen to obtain a silicon-carbon coated precursor;
[0148] (5) The obtained silicon-carbon coated precursor was placed in a porcelain boat and heated in a tube furnace at 5 °C min under an argon atmosphere. -1 The temperature was raised to 900°C at a rate of , then kept at that temperature for 3 hours, and naturally cooled to room temperature to obtain a silicon-carbon coated material.
[0149] Preparation Example 3
[0150] (1) 75 g of silicon powder (single crystal silicon, silicon purity of 99.999%, particle size range of 2 μm to 10 μm) was added to 1500 mL of ethanol solution, and the mixture was sand-milled at a speed of 2200 r / min for 8 h in a sand mill under nitrogen protection to obtain a nano-silicon slurry. The weight of the silicon powder was 5 g relative to 100 mL of organic solvent, and the average particle size D50 of solid nano-silicon in the obtained nano-silicon slurry was 29.1 nm;
[0151] (2) taking 40 mL of the nano-silicon slurry prepared in step (1) (the mass of silicon is 2 g), adding 2.0 g of L-malic acid (the first carbon source), stirring and dissolving and dispersing, the weight ratio of the first carbon source to the silicon source is 1:1, and the conditions of the primary in-situ coating reaction include: reaction temperature of 30° C., reaction time of 2 h, stirring rate of 500 r / min, and obtaining malic acid primary coated nano-silicon slurry;
[0152] (3) adding 1.0 g of dopamine hydrochloride (second carbon source) to the malic acid primary coated nano-silicon slurry prepared in step (2), wherein the weight ratio of the second carbon source to the first carbon source is 0.5:1, and stirring is continued for 1 h at room temperature at a stirring rate of 500 r / min to obtain a nano-silicon slurry coated by in-situ reaction of dopamine and malic acid;
[0153] (4) Take 2.0g of asphalt (2.0g of carbonizable binder, the weight ratio of carbonizable binder to silicon source is 1:1) and add it to the nano-silicon slurry prepared in step (3), continue stirring at room temperature for 1h, then add 18g of artificial graphite (the third carbon source, the weight ratio of the third carbon source to the silicon source is 9:1) and further mix, the reaction temperature is 30°C, the reaction time is 2h, the stirring rate is 500r / min, after stirring evenly, spray drying, the feed temperature is 140°C, the outlet temperature is 75°C, the carrier gas flow rate is 40L / min, the inlet pressure is 0.2MPa, and the carrier gas is nitrogen to obtain a silicon-carbon coated precursor;
[0154] (5) The obtained silicon-carbon coated precursor was placed in a porcelain boat and heated in a tube furnace at 5 °C min under an argon atmosphere. -1 The temperature was raised to 900°C at a rate of , then kept at that temperature for 3 hours, and naturally cooled to room temperature to obtain a silicon-carbon coated material.
[0155] Preparation Example 4
[0156] (1) 75 g of silicon powder (single crystal silicon, silicon purity of 99.999%, particle size range of 2 μm to 10 μm) was added to 1500 mL of ethanol solution, and the mixture was sand-milled at a speed of 2200 r / min for 9 h under nitrogen protection to obtain nano-silicon slurry. The weight of the silicon powder was 5 g relative to 100 mL of organic solvent, and the particle size range of solid nano-silicon in the obtained nano-silicon slurry was 27 nm;
[0157] (2) taking 40 mL of the nano-silicon slurry prepared in step (1) (the mass of silicon is 2 g), adding 2.0 g of citric acid (the first carbon source), stirring and dissolving and dispersing, the weight ratio of the first carbon source to the silicon source is 1:1, and the conditions of the primary in-situ coating reaction include: reaction temperature of 25°C, reaction time of 2 h, stirring rate of 450 r / min, and obtaining citric acid primary coated nano-silicon slurry;
[0158] (3) adding 1.0 g of melamine (second carbon source) to the citric acid primary coated nano-silicon slurry prepared in step (2), with the weight ratio of the second carbon source to the first carbon source being 0.5:1, and continuing stirring at room temperature for 1 h at a stirring rate of 500 r / min to obtain a nano-silicon slurry coated by in-situ reaction of melamine and citric acid;
[0159] (4) Take 0.5g sodium carboxymethyl cellulose and 2.0g asphalt (a total of 2.5g of carbonizable binder, the weight ratio of carbonizable binder to silicon source is 1.25:1) and add to the nano-silicon slurry prepared in step (3), continue stirring at room temperature for 1h, then add 12g of artificial graphite (the third carbon source, the weight ratio of the third carbon source to the silicon source is 6:1) and further mix, the reaction temperature is 25°C, the reaction time is 2h, the stirring rate is 300r / min, after stirring evenly, spray drying, the feed temperature is 160°C, the outlet temperature is 85°C, the carrier gas flow rate is 50L / min, the inlet pressure is 0.3MPa, and the carrier gas is nitrogen to obtain a silicon-carbon coated precursor;
[0160] (5) The obtained silicon-carbon coated precursor was placed in a porcelain boat and heated in a tube furnace at 5 °C min under an argon atmosphere. -1 The temperature was raised to 900°C at a rate of , then kept at that temperature for 3 hours, and naturally cooled to room temperature to obtain a silicon-carbon coated material.
[0161] Preparation Example 5
[0162] This preparation example refers to the method in Preparation Example 1, and the difference from Preparation Example 1 is that the ratio of raw material addition is changed, specifically including:
[0163] In step (2), 20 mL of the nano-silicon slurry prepared in step (1) (silicon mass is 1 g) is added to 2 g of ascorbic acid (first carbon source), and the mixture is stirred and dissolved and dispersed, wherein the weight ratio of the first carbon source to the silicon source is 1:0.5, and an in-situ coating reaction is performed to obtain ascorbic acid primary coated nano-silicon slurry;
[0164] In step (3), 1 g of dopamine hydrochloride (second carbon source) is added to the ascorbic acid primary coated nano-silicon slurry prepared in step (2), and the weight ratio of the second carbon source to the first carbon source is 1:2, i.e., 0.5:1, and a secondary in-situ coating is performed to obtain a nano-silicon slurry coated with dopamine and ascorbic acid in-situ reaction;
[0165] In step (4), 1 g of asphalt and 1 g of carboxymethyl cellulose (a total of 2 g of carbonizable binder, the weight ratio of the carbonizable binder to the silicon source is 2:1) are added to the nano-silicon slurry prepared in step (3), and after continuing to stir at room temperature for 1 hour, 40 g of artificial graphite (the third carbon source, the weight ratio of the third carbon source to the silicon source is 40:1) is added and further mixed to obtain a silicon-carbon coated precursor;
[0166] The remaining process is the same as that in Preparation Example 1 to obtain a silicon-carbon coated material.
[0167] Preparation Example 6
[0168] This preparation example refers to the method in Preparation Example 1, and the difference from Preparation Example 1 is that the ratio of raw material addition is changed, specifically including:
[0169] In step (2), 40 mL of the nano-silicon slurry prepared in step (1) (silicon mass is 2 g) is added to 0.25 g of ascorbic acid (first carbon source), and the mixture is stirred and dissolved and dispersed, wherein the weight ratio of the first carbon source to the silicon source is 1:8, and an in-situ coating reaction is performed to obtain ascorbic acid primary coated nano-silicon slurry;
[0170] In step (3), 0.1 g of dopamine hydrochloride (second carbon source) is added to the ascorbic acid primary coated nano-silicon slurry prepared in step (2), the weight ratio of the second carbon source to the first carbon source is 0.4:1, and a secondary in-situ coating is performed to obtain a nano-silicon slurry coated with dopamine and ascorbic acid in-situ reaction;
[0171] In step (4), 0.5 g of asphalt and 0.5 g of carboxymethyl cellulose (a total of 1 g of carbonizable binder, a weight ratio of the carbonizable binder to the silicon source of 0.5:1) are added to the nano-silicon slurry prepared in step (3), and after stirring for 1 h at room temperature, 12 g of artificial graphite (a third carbon source, a weight ratio of the third carbon source to the silicon source of 6:1) is added and further mixed to obtain a silicon-carbon coated precursor;
[0172] The remaining process is the same as that in Preparation Example 1 to obtain a silicon-carbon coated material.
[0173] Preparation Example 7
[0174] This preparation example refers to the method in Preparation Example 1, and the difference from Preparation Example 1 is that the process conditions are changed, specifically including:
[0175] In step (1), the nano-silicon slurry is obtained after being sand-milled at a speed of 2500 r / min for 50 h, wherein the average particle size D50 of the solid nano-silicon in the obtained nano-silicon slurry is 42.7 nm;
[0176] In step (2), the conditions of the primary in-situ coating reaction include: reaction temperature of 30° C., reaction time of 4 h, stirring rate of 600 r / min, and obtaining ascorbic acid primary coated nano-silicon slurry;
[0177] In step (3), the conditions for the secondary in-situ coating reaction include: stirring at 30° C. for 4 h and a stirring rate of 600 r / min to obtain a nano-silicon slurry coated with dopamine and ascorbic acid by in-situ reaction;
[0178] In step (4), the conditions of the three in-situ coating reactions include: reaction temperature of 30°C, reaction time of 4h, stirring rate of 600r / min, spray drying after uniform stirring, feed temperature of 180°C, outlet temperature of 100°C, carrier gas flow rate of 60L / min, inlet pressure of 0.4MPa, carrier gas of nitrogen, to obtain a silicon-carbon coated precursor;
[0179] In step (5), the obtained silicon-carbon coated precursor is placed in a porcelain boat and heated in a tube furnace at 5°C min -1 The temperature was raised to 1100°C at a rate of , then kept at that temperature for 3 hours, and naturally cooled to room temperature to obtain a silicon-carbon coated material.
[0180] Preparation Example 8
[0181] This preparation example refers to the method in Preparation Example 1, and the difference from Preparation Example 1 is that the process conditions are changed, specifically including:
[0182] In step (1), the nano-silicon slurry is obtained after being sand-milled at a speed of 2500 r / min for 52 hours, wherein the average particle size D50 of the solid nano-silicon in the obtained nano-silicon slurry is 33.9 nm;
[0183] In step (2), the conditions of the primary in-situ coating reaction include: reaction temperature of 30° C., reaction time of 0.25 h, stirring rate of 600 r / min, to obtain ascorbic acid primary coated nano-silicon slurry;
[0184] In step (3), the conditions for the secondary in-situ coating reaction include: stirring at 30° C. for 12 h at a stirring rate of 600 r / min to obtain a nano-silicon slurry coated with dopamine and ascorbic acid by in-situ reaction;
[0185] In step (4), the conditions of the three in-situ coating reactions include: reaction temperature of 30°C, reaction time of 12h, stirring rate of 600r / min, spray drying after stirring evenly, feed temperature of 220°C, outlet temperature of 120°C, carrier gas flow rate of 50L / min, inlet pressure of 0.5MPa, carrier gas of nitrogen, to obtain a silicon-carbon coating precursor;
[0186] In step (5), the obtained silicon-carbon coated precursor is placed in a porcelain boat and heated in a tube furnace at 5°C min -1 The temperature was raised to 1200°C at a rate of , then kept at that temperature for 3 hours, and naturally cooled to room temperature to obtain a silicon-carbon coated material.
[0187] The composition, content, structural characteristics and other data of the products obtained in the above preparation examples and comparative examples are listed in the following Table 1.
[0188] Table 1
[0189]
[0190] In Table 1, the symbol “ / ” in the thickness of the carbon coating layer indicates that the delamination boundary is not clear or there is no obvious delamination.
[0191] The following test examples are used to illustrate the electrochemical properties of the nano-carbon silicon composite materials provided in the preparation examples and comparative examples of the present disclosure.
[0192] Test cases 1 to 8
[0193] The nano-carbon silicon composite materials prepared in Preparation Examples 1 to 8 were mixed with acetylene black and a binder (the binder was sodium carboxymethyl cellulose and styrene-butadiene rubber, the mass ratio of the two was 1:1) at a mass ratio of 8:1:1 to form a slurry, which was coated on a copper foil and dried to obtain an electrode sheet. The prepared electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, and a Celgard 2400 type separator was selected, 1 mol L -1 LiPF 6 The electrolyte was a mixed solvent of ethylene carbonate: dimethyl carbonate: diethyl carbonate = 1:1:1. The button half-cell was assembled in a glove box and the battery was charged and discharged using a blue power system. The parameters were set as follows: current density 100 mA g -1 , the voltage range is 0.01~2.0V.
[0194] Comparative test examples 1 to 4
[0195] The test was carried out according to the method of Test Example 1, except that the nano-carbon-silicon composite material obtained in Preparation Example was replaced by the products obtained in Comparative Preparation Examples 1 to 4 respectively.
[0196] The test results of the above test examples and comparative test examples are listed in Table 2 below.
[0197] Table 2
[0198]
[0199] The first charge-discharge curve of Test Example 1 (using the composite material obtained in Preparation Example 1) is as follows: Figure 4 As shown, the charge and discharge cycle curve is as follows Figure 5 As shown by Figure 5 It can be seen that the two charge and discharge lines are highly overlapped and difficult to distinguish in the attached figure, indicating that the composite material obtained in Preparation Example 1 has good performance and stable charge and discharge performance.
[0200] The rate performance cycle curve of Test Example 1 (using the composite material obtained in Preparation Example 1) is as follows: Figure 6 As shown (including 0.1C / 0.2C / 0.5C / 1.0C / 2.0C charging and discharging, the charging and discharging voltage is limited to 0.01V~2.0V), it can be seen from the figure that the silicon-carbon coated composite material provided in the preparation example of the present disclosure has good rate performance; and Figure 5 The charging and discharging curves at different current densities are highly consistent, which further illustrates the stable performance of the composite material.
[0201] Comparing Test Example 1 with Comparative Test Examples 1 to 4, Comparative Test Examples 1 to 4 used composite materials prepared in Comparative Examples 1 to 4, and Comparative Examples 1 to 4 did not prepare composite materials according to the method provided in the present disclosure. Compared with Comparative Test Examples 1 to 4, Test Example 1 used the composite material obtained in Preparation Example 1, and Test Example 1 obtained a higher first coulombic efficiency and cycle capacity retention rate;
[0202] Comparing Test Example 5 with Test Example 6, it can be seen that the composite material used in Test Example 5 is prepared according to the addition ratio provided in the present disclosure during the preparation process. Compared with Test Example 6, Test Example 5 can achieve higher first coulombic efficiency and cycle capacity retention rate;
[0203] By comparing Test Example 1 with Test Example 7, it can be seen that the composite material used in Test Example 1 is prepared according to the optimized conditions provided in the present disclosure during the preparation process. Compared with Test Example 7, Test Example 1 can achieve higher first coulombic efficiency and cycle capacity retention rate.
[0204] By comparing Test Example 7 with Test Example 8, it can be seen that Test Example 7 uses the composite material prepared by Example 7. Compared with Test Example 8 which uses the composite material prepared by Example 8, Test Example 7 has a first charge specific capacity and a first coulombic efficiency that are significantly higher than those of Test Example 8 on the basis of good cycle stability.
[0205] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0206] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0207] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a carbon-silicon composite material, characterized in that: The following steps are involved: S1, mixing a silicon source with an organic solvent, and crushing the mixture to obtain a nano-silicon slurry; S2, contacting the nano-silicon slurry with a first carbon source to perform an in-situ coating reaction to obtain a primary coated nano-silicon slurry, wherein the first carbon source includes an organic acid; S3, contacting the primary coated nano-silicon slurry with a second carbon source to perform a secondary in-situ coating reaction to obtain a secondary coated nano-silicon slurry, wherein the second carbon source includes an organic amine; S4, contacting the secondary coated nano-silicon slurry with a carbonizable binder and a third carbon source, performing three in-situ coating reactions to obtain a carbon-silicon composite material precursor, wherein the third carbon source includes a graphite carbon source; S5, calcining the carbon-silicon composite material precursor under an inert atmosphere.
2. The method according to claim 1, characterized in that In step S1, the silicon source is a single-substance silicon powder; optionally, the single-substance silicon powder includes single-crystal silicon and / or polycrystalline silicon; optionally, the particle size of the single-substance silicon powder ranges from 1 μm to 10 μm; Optionally, the organic solvent is selected from one or more of an alcohol organic solvent, a hydrocarbon organic solvent and a benzene organic solvent; Preferably, the alcohol organic solvent is selected from one or more of ethanol, propanol and isopropanol; The hydrocarbon organic solvent is selected from one or more of hexane, cyclohexane and isooctane; The benzene organic solvent is selected from one or more of benzene, toluene and xylene; Preferably, the weight of the silicon source is 3 g to 20 g, preferably 5 g to 15 g, relative to 100 mL of the organic solvent.
3. The method according to claim 1, characterized in that: In step S1, the crushing treatment method includes mechanized crushing treatment by sand milling; preferably, the conditions of the mechanized crushing treatment by sand milling include: sand milling in a sand mill under an inert atmosphere, the sand mill speed is 2000r / min to 2500r / min, and the sand milling time is 4 to 50h, preferably 6 to 20h; Preferably, the D50 particle size range of the solid nano-silicon in the nano-silicon slurry obtained through the crushing treatment is 5 nm to 150 nm, preferably 30 nm to 100 nm.
4. The method according to claim 1, characterized in that: In step S2, the weight ratio of the first carbon source to the silicon source is 1:0.2-5, preferably 1:0.5-5; Preferably, the organic acid comprises one or more of a hydroxyl-containing organic carboxylic acid and a hydroxyl-containing carboxylic acid ester; Optionally, the hydroxyl-containing organic carboxylic acid is selected from one or more of tartaric acid, citric acid, lactobionic acid, malic acid and glutamic acid; Preferably, the hydroxyl-containing carboxylic acid ester comprises ascorbic acid; Preferably, the organic acid is selected from one or more of citric acid, tartaric acid and malic acid.
5. The method according to claim 1, characterized in that: In step S2, the conditions of the primary in-situ coating reaction include: reaction temperature of 15°C to 60°C, reaction time of 0.25h to 4h; preferably, reaction temperature of 20°C to 30°C, reaction time of 0.5h to 2h; optionally, stirring rate of 200r / min to 600r / min, preferably 300r / min to 450r / min.
6. The method according to claim 1, characterized in that In step S3, the weight ratio of the second carbon source to the first carbon source is 0.1 to 2:1, preferably 0.3 to 1.2:1, and more preferably 0.4 to 1:1; Preferably, the organic amine is selected from one or more of melamine and its ammonium salt, dopamine and its ammonium salt, hexamethylenetetramine and its ammonium salt; preferably, the organic amine is selected from one or both of dopamine and melamine.
7. The method according to claim 1, characterized in that In step S3, the conditions of the secondary in-situ coating reaction include: the reaction temperature is 15°C to 60°C, and the reaction time is 0.25h to 4h; preferably, the reaction temperature is 20°C to 30°C, and the reaction time is 0.5h to 2h; optionally, the stirring rate is 200r / min to 600r / min, preferably 300r / min to 450r / min.
8. The method according to claim 1, characterized in that: In step S4, the weight ratio of the carbonizable binder to the silicon source is 0.1 to 2:1, preferably 0.1 to 1:1; Optionally, the carbonizable binder is selected from one or more of asphalt, sodium carboxymethyl cellulose and lithium carboxymethyl cellulose; Preferably, in step S4, the weight ratio of the third carbon source to the silicon source is 4 to 50:1, preferably 6 to 40:1; Optionally, the graphite carbon source is selected from one or more of natural graphite, artificial graphite and flake graphite; preferably, the graphite carbon source is selected from one or more of natural graphite and artificial graphite having a spherical structure.
9. The method according to claim 1, characterized in that: In step S4, the conditions of the three in-situ coating reactions include: a reaction temperature of 15°C to 60°C, a reaction time of 0.25h to 4h; preferably, a reaction temperature of 20°C to 30°C, a reaction time of 0.5h to 2h; optionally, a stirring rate of 200r / min to 600r / min, preferably 300r / min to 400r / min; Preferably, step S4 further comprises spray drying the mixed slurry obtained by the three in-situ coating reactions to obtain the carbon-silicon composite material precursor; preferably, the conditions of the spray drying process include: a feed temperature of 120°C to 220°C, an outlet temperature of 80°C to 120°C, a carrier gas flow rate of 10L / min to 100L / min, an inlet pressure of 0.1MPa to 0.6MPa, and the carrier gas is selected from one or more of nitrogen and argon; Preferably, the feed temperature is 140°C to 180°C, the outlet temperature is 80°C to 100°C, the carrier gas flow rate is 30L / min to 60L / min, and the inlet pressure is 0.2MPa to 0.4MPa.
10. The method according to claim 1, characterized in that In step S5, the conditions of the calcination treatment include: a calcination temperature of 600°C to 1100°C, and a calcination time of 0.5h to 6h; preferably, a calcination temperature of 800°C to 1000°C, and a calcination time of 1h to 3h; Optionally, the heating rate is 1°C / min to 10°C / min, preferably 3°C / min to 5°C / min; The inert atmosphere is selected from one or more of argon and nitrogen.
11. A carbon-silicon composite material prepared according to the method according to any one of claims 1 to 10.
12. A carbon-silicon composite material, characterized in that: The carbon-silicon composite material comprises nano-silicon and a multi-layer heterogeneous carbon coating layer coated on the surface of the silicon matrix; the multi-layer heterogeneous carbon coating layer comprises a first carbon coating layer, a second carbon coating layer and a third carbon coating layer stacked in an outward direction from the surface of the nano-silicon; the second carbon coating layer contains nitrogen.
13. The carbon-silicon composite material according to claim 12, characterized in that: Based on the total weight of the carbon-silicon composite material, the content of silicon in the carbon-silicon composite material is 1% to 20% by weight, the content of carbon is 80% to 97% by weight, the content of nitrogen is 0.1% to 2% by weight, and the content of oxygen is 1% to 10% by weight; Preferably, the carbon-silicon composite material contains 1% to 10% by weight of silicon, 80% to 90% by weight of carbon, 0.1% to 0.5% by weight of nitrogen, and 3% to 10% by weight of oxygen.
14. The carbon-silicon composite material according to claim 12, characterized in that: The first carbon coating layer is an organic acid carbon coating layer, the second carbon coating layer is an organic amine carbon coating layer, and the third carbon coating layer is a graphite carbon coating layer; Preferably, in the carbon-silicon composite material, the total thickness of the multi-layer heterogeneous carbon coating layer is 10nm to 150nm, preferably 20nm to 100nm; Preferably, the thickness of the first carbon coating layer is 5nm to 40nm, the thickness of the second carbon coating layer is 5nm to 40nm, and the thickness of the third carbon coating layer is 10nm to 50nm; Optionally, the carbon-silicon composite material has an average particle size of 1 μm to 50 μm and a BET specific surface area of 1 m 2 / g~50m 2 / g; Preferably, the average particle size of the carbon-silicon composite material is 3 μm to 30 μm, and the BET specific surface area is 1 m 2 / g~10m 2 / g.
15. A negative electrode plate, characterized in that: The carbon-silicon composite material comprises any one of claims 11 to 14 of the present disclosure.
16. A lithium ion battery, characterized in that: Including the negative electrode sheet as described in claim 15.
Citation Information
Patent Citations
A nitrogen-doped carbon-silicon composite material and a method of manufacturing the same
CN108649197A
Silicon-carbon composite material, and preparation method and application thereof
CN112652742A
Silicon-carbon composite material and preparation method thereof
CN113659125A
High-density structured silicon-carbon composite material, manufacturing process and application thereof
DE102022102728A1